SISTEM KONTROL MESIN PENUKARAN UANG KERTAS RUPIAH BERBASIS PENGOLAHAN CITRA DAN RASPBERRY PI - Jalil, Abdul (ILKOM Jurnal Ilmiah, 2018)
The research purpose is to build a machine control system for exchange nominal of rupiahs paper money from big nominal to small nominal based on image processing and Raspberry Pi. The method for money exchange is detecting the authenticity of money, nominal of money, and amount of money exchange. The money authenticity was detected by the invisible image and nominal of money was detected by money color. Technique for detection the authenticity and nominal of money are using image processing that is processed on the Raspberry Pi. The algorithm used for detecting the authenticity and nominal of money are using template color algorithm and for exchange amount of money using the greedy algorithm. The research result is system able to detect the authenticity and nominal of paper money IDR 100.000, IDR 50.000, and IDR 20.000 then exchange it with the small nominal of money in accordance with the user choice.